Feedback Cheerleader, Mean-Spirited Feedback Estudio Critico Discursivo De Ideologias Sobre El Feedback Escrito En Un Departamento Universitario De Espanol En Estados Unidos - Dominguez-Mujica, Maria Eugenia (ProQuest LLC, 2012)
The aim of this research is to investigate ideologies that monitor and control styles of written feedback as well as discursive resources used in the expression of those ideologies. Using socio-cognitive analysis, a development of critical discourse studies, I have analyzed 44 sessions of chat on the Internet, 78 journal notes, 31 emails and 12 revisions of chat texts in Google docs. I worked with eight students from the University of Minnesota Department of Spanish and Portuguese: three undergraduate students in the Spanish major and five graduate students working as instructors of Spanish. They all chatted via Internet about written feedback and other topics. The collected data are counts of experiences, opinions and comments cross referenced with the views of respondents and the researcher. In the analysis, following van Dijk (2003, 2005a), the presence of ideology has been identified where controversy could be verified. Controversy has been defined by positive self-representation of those who share the same beliefs (ingroup) and the negative representation of others (outgroup). Discursive analysis of data showed two main controversial subjects regarding written feedback: quantity (if it should be extensive or not) and style (if it is necessary, should be enthusiastic, polite, honest, negative, etc.). Accordingly, students were classified into two social groups with different educational traditions. Within the American tradition, equality and individualism prevailed while, in Spanish speaking educative traditions, hierarchy and collectivism were the associated values. The most relevant discursive resources for the expression of ideological content were creation of vernacular terms, implications (direct and covert), negative intensifiers (bad words and derogatory terms), and code switching. The results validated the presentation of episodes and opinions (the researcher's own and those collected from other informants) as a methodology for the investigation of ideologies as ideologies are relatively stable cognitive units that do not change in the course of a conversation. However, analysis of the data has also shown that dialogue and the clash of opinions can slowly destabilize certain beliefs reaffirming the key role of language in the creation, transmission and perpetuation of ideologies. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]